Young adults' subjective and objective risk attitude in financial decision making: Evidence from the lab and the field. (2nd July 2018) - Oehler, Andreas; Horn, Matthias; Wedlich, Florian
Abstract : Purpose: The purpose of this paper is to derive the determinants of young adults' subjective and objective risk attitude in theoretical and real-world financial decisions. Furthermore, a comparison of the factors that influence young adults' and older adults' risk attitude is provided. Design/methodology/approach: The paper relies on an experimental setting and a cross-sectional field study using data of the German central bank's (Deutsche Bundesbank) PHF-Survey. Findings: Young adults' objective risk aversion is not constant but increases with stake sizes. Furthermore, young adults' subjective risk attitude is a better predictor for their objective risk attitude than a set of commonly employed socio-demographics and economics like age or income. Moreover, young adults' subjective risk attitude works as a mediator for the influence of their investable financial wealth on their objective risk attitude. Although young adults' subjective risk attitude shows a gender effect, the influence of young adults' gender on their objective risk attitude decreases with higher stake sizes. Compared to older adults, young adults generally show a similar degree of subjective risk aversion. However, due to stronger financial restrictions, young adults show a higher degree of objective risk aversion. Originality/value: Although individuals' financial outcomes depend on the financial behavior established in young adulthood, there is no study that simultaneously analyzes the determinants of young adults' subjective and objective risk attitude in real-world financial decisions with a focus on young adults as a separate age group. The paper closes this gap in literature and additionally provides a comparison of the subsamples of young adults and older adults. The analysis in this paper reveals that young adults' lower engagement in financial markets is primarily driven by their tight budget and not by a fundamental different subjective risk attitude.